2021
DOI: 10.15252/embj.2021108605
|View full text |Cite
|
Sign up to set email alerts
|

Commensal microbiota divergently affect myeloid subsets in the mammalian central nervous system during homeostasis and disease

Abstract: The immune cells of the central nervous system (CNS) comprise parenchymal microglia and at the CNS border regions meningeal, perivascular, and choroid plexus macrophages (collectively called CNS‐associated macrophages, CAMs). While previous work has shown that microglial properties depend on environmental signals from the commensal microbiota, the effects of microbiota on CAMs are unknown. By combining several microbiota manipulation approaches, genetic mouse models, and single‐cell RNA‐sequencing, we have cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…Meanwhile, PVMs participated in experimental allergic encephalomyelitis (EAE) or hypertension. Polfliet MMJ, 85,104 Galea I, 105 and Faraco G 52 were representative researchers of Vrije Univ Amsterdam whose research directions were perivascular and meningeal macrophages in EAE or hypertension. EAE had the longest emergence time of keywords burst from 1997 to 2007, meaning researchers continued to pay attention to them, which is also consistent with the result of cluster analysis 44,85 …”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, PVMs participated in experimental allergic encephalomyelitis (EAE) or hypertension. Polfliet MMJ, 85,104 Galea I, 105 and Faraco G 52 were representative researchers of Vrije Univ Amsterdam whose research directions were perivascular and meningeal macrophages in EAE or hypertension. EAE had the longest emergence time of keywords burst from 1997 to 2007, meaning researchers continued to pay attention to them, which is also consistent with the result of cluster analysis 44,85 …”
Section: Discussionmentioning
confidence: 99%
“…This notion has encouraged several probiotic treatment approaches. Indeed, application of probiotic bacterial strains alleviated DSS-induced colitis, reduced systemic and CNS cytokine levels, induced micro-RNA expression related to restoring inflammation-associated microbiota dysbiosis, and improved depressive and anxiety-like behavior [ 146 , 147 , 148 , 149 ]. However, it is unclear whether effects of probiotic treatments were solely indirect based on the reduction in gut inflammation or also directly interfered with inflammatory gut-to-brain communication or neurons.…”
Section: Impact Of Microbiota On Neuroinflammation and Neuropsychiatr...mentioning
confidence: 99%
“…First, microbiota and microbiota-derived molecules actively shape the CNS immune landscape, and the presence of a complex microbiota is essential for microglia activation and function [ 148 , 150 , 151 , 152 ]. Among other CNS-associated myeloid cell types, commensal microbiota strongly influence CP macrophages, while their impact on perivascular and meningeal macrophages is moderate [ 148 ]. Different microbial metabolites were described to modulate microglia.…”
Section: Impact Of Microbiota On Neuroinflammation and Neuropsychiatr...mentioning
confidence: 99%
“…It was revealed that cpMΦ are responsive to the absence of the microbiome. Additionally, gut microbiota influences the Aβ uptake of pvMΦ in 5xFAD mice (Sankowski et al, 2021 ). Further, CAMs in GF mice lack an appropriate response to immunostimulants typically characterized by expansion and expression of CD74.…”
Section: Influence Of the Microbiome On Cns Macrophagesmentioning
confidence: 99%
“…Further, CAMs in GF mice lack an appropriate response to immunostimulants typically characterized by expansion and expression of CD74. These findings suggest that the innate immune response depends on the presence of microbiota in the GIT and absence of the microbiome disrupts innate immunity (Sankowski et al, 2021 ). The gut microbiota has a major influence on CNS macrophages during development until adulthood and their metabolites govern the inflammatory response in the CNS, which is mediated by macrophages.…”
Section: Influence Of the Microbiome On Cns Macrophagesmentioning
confidence: 99%